2019
DOI: 10.1139/cjpp-2018-0228
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with atorvastatin against renal ischemia–reperfusion injury in nondiabetic versus diabetic rats

Abstract: Acute renal failure complicates renal ischemia–reperfusion (I/R) owing to reactive oxygen species production. Atorvastatin (ATO) has anti-inflammatory and antioxidant properties. The current study investigated whether ATO alleviated damage induced by renal I/R injury in nondiabetic versus diabetic rat models. Thirty-six rats were equally divided into 6 groups: group A1 (nondiabetic sham), group A2 (nondiabetic I/R), group A3 (nondiabetic ATO + I/R), group B1 (diabetic sham), group B2 (diabetic I/R), and group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Thus, the administration of antioxidants that counteract oxidative stress may protect kidneys from damage. Nephrotoxicity studies have confirmed the authentic roles of bioactive compounds to reduce chronic renal failure [27,[34][35][36]. The present study investigated CURC effects on OTA-induced toxicity using an in vivo animal model.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, the administration of antioxidants that counteract oxidative stress may protect kidneys from damage. Nephrotoxicity studies have confirmed the authentic roles of bioactive compounds to reduce chronic renal failure [27,[34][35][36]. The present study investigated CURC effects on OTA-induced toxicity using an in vivo animal model.…”
Section: Discussionmentioning
confidence: 72%
“…30 Atorvastatin was administered at 10 mg/kg dose. 31 We used atorvastatin in our study to compare effects of 5-HT7 receptors with an anti-atherogenic agent in MI induced damage in rats with underlying atherosclerosis. All control rats received distilled injectable water as vehicle for all applications.…”
Section: Experimental Protocols Of Iso-induced MImentioning
confidence: 99%
“…The CD44 and caspase-3 expression, oxidative stress, and kidney function biomarkers were improved in both groups. The study concluded that atorvastatin may have beneficial and protective effects on renal I/R injury in rats with or without diabetes [22].…”
Section: Resultsmentioning
confidence: 95%